Aos cuidadores do serviço residencial terapêutico: novas maneiras de cuidar...? - Ribeiro Neto, Pedro Machado (2009)
This work has proposed conducting an approximation of the reality of caretaker of a SRT to contribute to discussions on the Psychiatric Reform and deinstitutionalization of madness. We chose the qualitative approach because we believe that best apply to the proposed objectives. The study participants were six caretakers of a therapeutic residence of the State of Espírito Santo. For data collection was used semi-structured interviews and participant observation. For data analysis and interpretation were used the "Content Analysis" of the material collected, and prioritized the use of one of its categories, the "thematic analysis”. We found that caregivers are professionals who worked on common services basically, without a higher level of complexity, and also unrelated to the area of Health. All participants have less than a year of experience in the SRT. Were contracted of two companies: one specializing in food, and one of general services. Participants considered that were not prepared to act in the house, but despite this, they feel prepared for the service. Had no training in health, acquired the main information of the SRT on their first contact the HAB, which received guidance on their work in residential service. Besides the guidelines, learn to deal with situations, which were mainly concerned in the day to day work. Was noted that users, in general, are similar to the child several times in the speech of the participants, and the process of social reintegration is compared to the child learning. We suggest the creation of spaces where can be discussed with the caregivers and residents on issues such as health care, madness, and that the professional of residential services must have a considerably more comprehensive support for the conduct of their office. In this context, beyond inquire about which types of care are being practiced by caretakers of residential service for residents, we concluded that also indispensable discuss the level of attention given to caregivers.